Patient care experiences and perceptions of the patient-provider relationship: A mixed method study - Jennifer Tabler; Debra Scammon; Jaewhan Kim; Timothy Farrell; Andrada Tomoaia-Cotisel; Michael Magill (The Beryl Institute, 2014)
Improving interpersonal continuity of care-the personal relationship forged between a patient and their primary care provider (PCP) over time-is often considered a goal of primary care. Continuity of care is frequently assessed in terms of longitudinal continuity, or the proportion of encounters with one practitioner, overlooking aspects of the patient-provider relationship that are key to interpersonal continuity of care. Further, few studies explore patients' perspectives regarding which care experiences enhance or detract from the patient-provider relationship. This study, using focus group interviews, a patient experience CAHPS-PCMH survey, and electronic medical records, explored how patients' experiences at 10 primary care clinics influenced their perceptions of their relationship with their PCPs. Focus group interviews with 63 participants indicated that patients' experiences in the clinics, such as wait-times, influenced their perceptions of the patient-provider relationship. The relationship between patient experience and interpersonal continuity was empirically assessed using survey responses and medical records (n=645). We used patients' perceptions that their provider knows them as a person as a measure of interpersonal continuity. Logistic regression results indicated that being seen within 15 minutes, receiving visit reminders, effective provider communication, and satisfaction, positively influenced patient perceptions of the patient-provider relationship. Furthermore, patients' care experiences shaped their perceptions of the patient-provider relationship independent of their satisfaction with care. The mixed methods design adds depth to our understanding of patients' care experiences, and illustrates that these experiences are critical for understanding the patient-provider relationship. Future research on interpersonal continuity should take patient experiences into account.